The Impact of Nontuberculous Mycobacteria Species on Mortality in Patients With Nontuberculous Mycobacterial Lung Disease - Wang, Ping-Huai; Pan, Sheng-Wei; Wang, Su-Mei; Shu, Chin-Chung; Chang, Chin-Hao (Frontiers in Microbiology, 2022)
Patients with nontuberculous mycobacterial lung disease (NTM-LD) have increased mortality. The impact of NTM species on the risk of mortality remains unclear, especially that of death by non-cancer causes. We conducted a retrospective cohort study from 2006 to 2018 in a tertiary hospital in Taiwan. We enrolled patients who fulfilled the microbiologically diagnostic criteria of NTM-LD. Mortality causes within eight years after diagnosis were identified and Cox proportional hazard regression was performed for risk factors of mortality. A total of 1652 subjects with NTM-LD were included. Among them, 723 (43.8%) were infected by Mycobacterium avium complex (MAC), 408 (24.7%) by M. abscessus complex (MABC), 120 (7.3%) by M. kansasii (MK), 304 (18.4%) by other rapid growing mycobacteria (RGM) and 97 (5.9%) by other slow growing mycobacteria (SGM) groups. The 8-year all-cause mortality was 45.2% for all and highest in the MK-LD group (59.2%), followed by the MABC-LD and MAC-LD groups. The adjusted hazard ratios were 2.20 (95% confidence interval:1.40–3.46) in the MK-LD, 1.85 (1.54–2.22) in the MABC-LD, and 1.65 (1.12–2.41) in the MAC-LD groups for all-cause mortality, compared with the SGM group. Kaplan–Meier survival curves showed that all-cause mortality, non-cancer mortality, and mortality due to chronic airway diseases were significantly correlated with NTM species (log rank p = 0.0031, < 0.001, and 0.001, respectively). High eight-year mortality rates were found in patients with NTM-LDs according to different NTM species. Notably, the difference was significant in non-cancer mortality causes, especially in chronic airway disease.